Impact of CYP3A5 phenotype on tacrolimus concentrations after sublingual and oral administration in lung transplant. (15th April 2019) - Pasternak, Amy L; Kidwell, Kelley M; Dempsey, Jacqueline M; Gersch, Christina L; Pesch, Andrea; Sun, Yihan; Rae, James M; Hertz, Daniel L; Park, Jeong M
Aim: This study evaluated the impact of CYP3A5 genotype and other patient characteristics on sublingual (SL) tacrolimus exposure and compared the relationship with oral administration.Patients & methods: Tacrolimus concentrations were retrospectively collected for adult lung transplant recipients, who were genotyped for CYP3A5*3, CYP3A4*22, CYP3A7*1C, and POR*28 . Regression analyses were performed to determine covariates that impacted the SL and oral tacrolimus concentration/dose ratios.Results: An interaction of CYP3A5 genotype and CYP3A inhibitor increased the SL concentration/dose, while cystic fibrosis decreased the SL concentration/dose. The oral concentration/dose was independently associated with these covariates and was increased by serum creatinine and number of tacrolimus doses.Conclusion: This study suggests personalized dosing strategies for tacrolimus likely need to consider characteristics beyond CYP3A5 genotype.